Icariin as a potential anticancer agent: a review of its biological effects on various cancers - Liu, Fang-Yuan; Ding, Dan-Ni; Wang, Yun-Rui; Liu, Shao-Xuan; Peng, Cheng; Shen, Fang; Zhu, Xiao-Ya; Li, Chan; Tang, Li-Ping; Han, Feng-Juan (Frontiers in Pharmacology, 2023)
Numerous chemical compounds used in cancer treatment have been isolated from natural herbs to address the ever-increasing cancer incidence worldwide. Therein is icariin, which has been extensively studied for its therapeutic potential due to its antiinflammatory, antioxidant, antidepressant, and aphrodisiac properties. However, there is a lack of comprehensive and detailed review of studies on icariin in cancer treatment.Given this, this study reviews and examines the relevant literature on the chemopreventive and therapeutic potentials of icariin in cancer treatment and describes its mechanism of action. The review shows that icariin has the property of inhibiting cancer progression and reversing drug resistance. Therefore, icariin may be a valuable potential agent for the prevention and treatment of various cancers due to its natural origin, safety, and low cost compared to conventional anticancer drugs, while further research on this natural agent is needed.